The polyfactorial model of autism and the question of causality - Golse, Bernard (Frontiers in Psychiatry, 2023)
After recalling the different pediatric, psychopathological and child psychiatric models of mental disorders in children and adolescents, the author presents in detail the so-called polyfactorial model, which includes primary, secondary, and mixed factors. This model is the epistemological heir of the Freudian concept of “complementary series.” The example of autism is then explored as a paradigm of the usefulness of this polyfactorial model. Finally, we reflect on the notion of causality, from Aristotelian causality to epigenetic causality, which could 1 day re-legitimize psychoanalysis and the impact of the relationship on genome expression.